(3efGaY GdCUhds ((3LYaQ Hf eMeO Hf eMeO GdUaOi GdMSfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi cGTa GdZeI aEf Yde GdWH CLd GdeaGNQ hGced GdeBKQ aCYde Cf eHfi GdWH heOGQ CeQg Ydi eYQaI MGdJi HOf GdEfSGf s
(3BNQgG (B:s
(3hGdTH jYQV dTGQHgeG GdSYGd hjHS GdMdb hjDd MGdg ai GdCcKQ Edi GdSd hYdGLgG GdbF hTQH GddHf hGdRHO HGdScQ hGdCTQI GdCOgGf GdHGQOI GdeQWHI hGdCdYHI GdeOjfI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs